2015
DOI: 10.1111/poms.12334
|View full text |Cite
|
Sign up to set email alerts
|

Class‐Based Storage with a Finite Number of Items: Using More Classes is not Always Better

Abstract: C lass-based storage is widely studied in the literature and applied in practice. It divides all stored items into a number of classes according to their turnover. A class of items with higher turnover is allocated to a region closer to the warehouse depot. In the literature, it has been shown that the use of more storage classes leads to a shorter travel time for storing and retrieving items. A basic assumption in this literature is that the required storage space for all items equals their average inventory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 16 publications
(64 reference statements)
2
57
0
6
Order By: Relevance
“…In the general case, a bowl-shaped relationship exists between the time required to access the goods in the storage system and the number of classification categories (Yu et al 2015). It has been theoretically revealed that regardless of the quantity of goods, the optimal storage efficiency can always be achieved by classifying the goods into 3-5 categories.…”
Section: Clustering Analysis Of the Ordered Goodsmentioning
confidence: 99%
“…In the general case, a bowl-shaped relationship exists between the time required to access the goods in the storage system and the number of classification categories (Yu et al 2015). It has been theoretically revealed that regardless of the quantity of goods, the optimal storage efficiency can always be achieved by classifying the goods into 3-5 categories.…”
Section: Clustering Analysis Of the Ordered Goodsmentioning
confidence: 99%
“…He also determines the mean and variance of the travel times for AS/R systems for the two-class NSIT case. Recently, Yu et al (2015) determined optimal zone boundaries and showed that an optimal (small) number of zones exist, if space requirements are taken into account. Stadtler (1996), Sari et al (2005), Gue and Kim (2007), De Koster et al (2008), de Koster (2009), andZaerpour et al (2015b) study compact storage systems using different depth handling systems.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, function (10) implies that regardless of the values of w 1 , w 2 , w 3 , t A , t B , t C , a and A, the global optimum of E(D) never is going to be achieved in Case 2, Case 3, Case 5, Case 6, Case 7 or Case 8. In consequences, we can ignore those cases in the optimization process.…”
Section: |mentioning
confidence: 99%
“…In this way, class-based storage policies have a lower expected travel time to pick and retrieve loads when compared to randomize policies. Yu et al [10] showed that even if the storage classes decrease the expected travel time, a small number of classes is optimal when a discrete number of items for each class is considered. Their results are robust to different kinds of ABC-demand profiles and warehouse shape.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation